2014
DOI: 10.1039/c4lc00671b
|View full text |Cite
|
Sign up to set email alerts
|

On the flow topology inside droplets moving in rectangular microchannels

Abstract: The flow topology in moving microdroplets has a significant impact on the behaviour of encapsulated objects and hence on applications of the technology. This study reports on a systematic investigation of the flow field inside droplets moving in a rectangular microchannel, by means of micro-particle image velocimetry (µPIV). Various water/oil (w/o) fluid mixtures were studied in order to elucidate the effects of a number of parameters such as capillary number (Ca), droplet geometry, viscosity ratio and interfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
69
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 100 publications
(74 citation statements)
references
References 40 publications
3
69
1
1
Order By: Relevance
“…Another situation analogous to the ganglia in porous media is the movement of microfluidic droplets in micro-channels 3741 . Experimental and numerical works on liquid-liquid slug flows in capillary channels have shown internal recirculations within both phases, which were affected by capillary forces 42 , the viscosity ratio between the fluids 43,44 , the channel flow velocity and the slug size 45,46 . Low capillary numbers resulted in slower channel flows and large slugs caused the attenuation of recirculation zones inside the mobilised slugs.…”
Section: Introductionmentioning
confidence: 99%
“…Another situation analogous to the ganglia in porous media is the movement of microfluidic droplets in micro-channels 3741 . Experimental and numerical works on liquid-liquid slug flows in capillary channels have shown internal recirculations within both phases, which were affected by capillary forces 42 , the viscosity ratio between the fluids 43,44 , the channel flow velocity and the slug size 45,46 . Low capillary numbers resulted in slower channel flows and large slugs caused the attenuation of recirculation zones inside the mobilised slugs.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, it has been widely used to study the droplet flow topology of liquid-liquid systems in microfluidics. [23][24][25][26][27][28][29] However, to the best of our knowledge no µPIV study has reported on the flow conditions in double emulsions, especially those in inner cores of w/o/w double emulsions. All chemicals were purchased from Sigma Aldrich Co. UK, unless noted otherwise and used without further purification.…”
Section: Introductionmentioning
confidence: 99%
“…Microfluidic PDMS devices were fabricated by combined photo-and softlithography, 30 and have been described in detail previously. 29 particles per ml before flow delivery. The volume fraction of these seeding particles in flow was only 4 × 10 -6 , and hence no effect on the measured flow topology was expected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be explained qualitatively from the simulations, which clearly show that strong and uniform focusing occurs in systems with good acoustic matching between the droplet and the continuous phase (olive oil), while focusing is only maintained near the center of droplets having a poor acoustic matching with the continuous phase (fluorinated oil). The lack of focusing forces near the droplet ends is crucial in explaining the poor overall acoustophoretic behavior: as droplets move in microfluidic channels flow rolls are induced inside them (Kinoshita et al 2007;Ma et al 2014), and these flow rolls counteract the acoustic focusing force in the front of the droplet . Consequently, in acoustically mismatched droplets, the acoustic focusing is too weak to balance the defocusing Stokes' drag force from the flow rolls, and such droplets are unlikely to exhibit good acoustic particle focusing.…”
Section: Concluding Discussionmentioning
confidence: 99%